2009
DOI: 10.1007/s00011-009-0108-5
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum HY8004 attenuates TNBS-induced colitis by inhibiting lipid peroxidation in mice

Abstract: B. longum HY8004 can improve colitis via the inhibition of lipid peroxidation as well as NF-kappaB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…The common LAB genera are Lactobacillus sp., Lactococcus sp., Leuconostoc sp., Pediococcus sp., Enterococcus sp., Streptococcus sp., and Bifidobacterium sp isolated from fermented foods and intestinal microflora. These LAB are safe microorganisms that improve any disturbances of indigenous microflora [9,10], ameliorate the development of beneficial microflora [7], have anti-inflammatory (anticolitic and antivaginitic) effects [11][12][13], and induce non-specific activation of the host immune system [10]. Furthermore, some Lactobacillus strains isolated from the vaginal cavities of healthy women antagonize C. albicans by lowering the pH and/or producing metabolites, such as hydrogen peroxide and lactic acid, and antibacterial molecules, including bacteriocins [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The common LAB genera are Lactobacillus sp., Lactococcus sp., Leuconostoc sp., Pediococcus sp., Enterococcus sp., Streptococcus sp., and Bifidobacterium sp isolated from fermented foods and intestinal microflora. These LAB are safe microorganisms that improve any disturbances of indigenous microflora [9,10], ameliorate the development of beneficial microflora [7], have anti-inflammatory (anticolitic and antivaginitic) effects [11][12][13], and induce non-specific activation of the host immune system [10]. Furthermore, some Lactobacillus strains isolated from the vaginal cavities of healthy women antagonize C. albicans by lowering the pH and/or producing metabolites, such as hydrogen peroxide and lactic acid, and antibacterial molecules, including bacteriocins [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The common LAB genera are Lactobacillus sp., Lactococcus sp., Leuconostoc sp., Pediococcus sp., Enterococcus sp., Streptococcus sp., and Bifidobacterium sp., which can be isolated from fermented foods and intestinal microflora. These LAB are safe microorganisms that improve any disturbances of indigenous microflora [13,14], ameliorate the ill effects of harmful microflora [11], have anti-inflammatory (anticolitic and antivaginitic) effects [15][16][17], and induce the non-specific activation of the host immune system [14]. Furthermore, some Lactobacillus strains isolated from the vaginas of healthy women antagonize vaginosis-associated G. vaginalis by lowering of the pH and/or by producing metabolites, such as, hydrogen peroxide, lactic acid, and antibacterial molecules, including bacteriocins [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the current results, a positive control, sulfasalazine did not show the significance. It has been reported that sulfasalazine has effects on IBD and used in IBD animal experiments as positive control (Lee et al, 2010b;Zhao et al, 2010). We thought the reason why sulfasalazine showed no significant effect in DSS model may be come from different mice strain, dosage, DSS concentration and period of observation (Singh et al, 2009;Lee et al, 2010b).…”
Section: Discussionmentioning
confidence: 95%